An acute life-threatening episode of rhabdomyolysis, renal failure, altered mental status and hyperammonemia in an adult with 3-methylcrotonyl-CoA carboxylase deficiency - Rachel McGowan; Shoji Yano (Molecular Genetics and Metabolism Reports)
3-methylcrotonyl-CoA carboxylase (3-MCC) deficiency is an autosomal recessive disorder of leucine metabolism. Since 3-MCC deficiency is thought to be a benign condition, a few newborn screening programs discontinued to screen this condition. We report a case of a 24-year-old previously healthy male patient who developed generalized rhabdomyolysis, weakness, respiratory and renal failure, acute pancreatitis, hyperammonemia, and altered consciousness after strenuous exercise. Diagnosis of 3-MCC was made based on increased plasma C5OH carnitine, urine 3-methylcrotonylglycine, and 3-hydroxyisovalerate, and later whole genome sequencing study confirmed the diagnosis. Low plasma carnitine and high creatine kinase (CK) levels were again noted after two months of poor compliance with carnitine therapy. Since 3-MCC deficiency is often incidentally diagnosed in asymptomatic mothers through positive newborn screening in the newborns and most positive newborn screening cases have benign clinical outcomes, 3-MCC deficiency has been considered a benign condition. Observation of a life-threatening episode triggered by strenuous exercise and recurrent occurrence of low carnitine and high CK without carnitine supplementation may support 3-MCC deficiency to be the condition covered by the newborn screen since carnitine supplementation likely prevents an episode that can be life-threatening. Asymptomatic adults with 3-MCC deficiency may benefit from periodic evaluation of plasma carnitine levels.